Failure of Persatuan Pembangunan Party to Pass The Parliamentary Threshold In The 2024 Elections: An Analysis From The Perspective of Party Institutionalization - Subekti, Dimas; Wahid, Makmun; Yusuf, M; Sa'adah, Maratun (Politeia: Jurnal Ilmu Politik, 2025)
The purpose of this research is to analyze the failure of the PPP in the 2024 elections using the perspective of political party institutionalization. This research uses a qualitative method with a case study approach. The data collection technique in this research is a literature study. The findings of this study explain that PPP's failure to qualify for parliament in the 2024 elections is dominated by its very poor institutionalization factor. On the root of society indicator, the PPP failed in two ways, namely the party elite's poor psychological reading of its voter base and its slowness in understanding the importance of transforming internal changes, which resulted in a significantly underdeveloped social mass base. Then, the autonomy indicator explains that PPP does not fully have autonomy in making decisions regarding the nomination of candidates for the 2024 elections. On the Level of organization indicator, PPP also experienced a very acute and prolonged management conflict problem. This has made PPP's image in the community very bad. Finally, the coherence indicator shows that PPP is weak in consolidating cadres and sympathizers, which has an impact on the lack of solidarity in following the decisions taken by the party for the 2024 elections.